A sense of belonging : Today’s pinball playing as a contribution to good mental health. - Jens Peter Eckardt (Journal of Games, Game Art, and Gamification, 2023)
The purpose of this perspective is to address the mental health concept of belonging generated by the playing of pinball machines today. By looking at academic papers and literature written on pinball machines and the concept of belonging together with a highlight of a specific research paper from 1973, it is argued that engagement in pinball playing may promote a sense of belonging as a subjective feeling of deep connection with a social group, which is associated with enhanced mental well-being. In that sense on research into the development of digital and video gaming, pinball playing thus still constitutes an important link in their history, development, and the encouragement of connectedness.